Molecular dissociation in presence of a catalyst: II. The bond breaking role of the transition from virtual to localized states - Ruderman, Andres (2016)
Weaddress a molecular dissociation mechanism that is known to occur when aH2 molecule approaches a catalyst with its molecular axis parallel to the surface. It is found that molecular dissociation is a form of quantum dynamical phase transition associated to an analytic discontinuity of quite unusual nature: the molecule is destabilized by the transition from non-physical virtual states into actual localized states. Current description complements our recent results for a molecule approaching the catalyst with its molecular axis perpendicular to the surface (Ruderman et al 2015 J. Phys.: Condens. Matter 27 315501). Also, such a description can be seen as a further successful implementation of a non-Hermitian Hamiltonian in a well defined model.